Meningkatkan Kemampuan Bernalar Kritis melalui model Problem Based Learning (PBL) Berbantuan Lembar Kerja Peserta Didik (LKPD) Mata Pelajaran Pendidikan Agama Katolik Kelas XI SMK Negeri 1 Metro - Almateus Nanang Rudiatmoko (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This study aims to improve students' critical reasoning abilities in the matter of church assignments through the application of the Problem Based Learning (PBL) Model assisted by Student Worksheets (LKPD) in the subject of Catholic Religious Education Phase F class XI at SMK Negeri 1 Metro This research aims to improve students' achievement and critical reasoning abilities in church assignments material through the application of the Problem Based Learning (PBL) Model in Catholic Religious Education Subject Phase F Class XI Odd Semester 2023/2024 academic year. The problem faced is the low understanding and application of students' critical reasoning abilities in carrying out church tasks. The results of the study show that the application of the PBL method in church assignments material significantly increases the understanding and application of students' critical reasoning abilities. Students are actively involved in the process of solving problems, discussing, and formulating solutions that describe students' critical reasoning abilities. This research provides benefits for students, teachers, and educational institutions. Students can develop a better understanding of critical reasoning skills and understanding in church tasks and everyday life. Teachers can use the PBL method as an effective learning strategy in increasing the understanding and application of the value of critical thinking skills